Awareness of dental fluorosis among undergraduate dental students in Riyadh region: a survey based study - AlDaiji, Reem; Alotaibi, Malak; Alnowaiser, Dania; Albahely, Rawan; Bachat, Rama; Alshayea, Alaa; Alotaibi, Fatima (International Journal of Research in Medical Sciences, 2018)
Background: Fluoride protects the teeth from dental caries using the needed amount of fluoride products. Methods: A Modified structured questionnaire has been validated through a pilot trial (20 responses) prior to administration that contains16 questions was distributed. Other than the demographics, the data were collected from 500 participants including undergraduate male and female dental students. Results: The majority described the mild fluorosis appearance in the teeth according to Dean’s index appropriately as white opacity of the enamel (64%, n=320). On the other hand, only 31.1% (n=155) and 46% (n=229) described the moderate and severe fluorosis appearance in the teeth according to Dean’s index appropriately. Conclusions: The dissemination and education about dental fluorosis is urgently needed and should be tailored to reach this population. The knowledge about causes of fluoride and the effect on dental fluorosis should be presented in the education.